Students’ Perception of Learning Vocabulary Through Duolingo Application: The Case of Secondary School in Banyuwangi - Annisatuz Zakiyah; St. Shabibatul Rohmah; Imro’atul Husna Afriani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Duolingo is an interesting English learning application and solution if you want to learn English vocabulary independently. And this is a gamification application, which means users can learn English by playing games because this application uses audio visuals when learning. The aim of this research are to determine the perception of foreign language English (EFL) in using the Duolingo application in vocabulary learning, and to provide students experience and motivation when interacting with Duolingo. This research design uses a qualitative research design with a descriptive analysis approach. Participants in this research were 21 students in class XII A of Madrasah Aliyah Nahdatul Wathan for the 2024 ⁄ 2025 academic year. To collect research data, questionnaires and interviews were conduct 10 students. When conducting observations at schools, researchers found obstacles, namely a lack of interest and motivation when learning English and they had never previously studied English through applications. Based on this situation, researchers used the Duolingo application as a learning medium that students can use to develop a diverse English vocabulary. The research results show that using the Duolingo application in class XII A can give them opportunity to learn English in a fun way and provide a unique experience when learning vocabulary through the Duolingo application. Most students give positive perceptions when learning vocabulary through the Duolingo application.